Arabic Language Acquisition in Indonesia’s Muslim Minority Community: A Netnographic Study in the Arab Village - Muhammad Zaki Mubarak; Muassomah; Leny Octriana (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Indonesian serves as both the primary means of communication and the mother tongue for the majority of the country's population. However, this is not the case for the community in Parmeraan Village, North Padang Lawas, where Arabic is adopted as the first language for their children. This study aims to explore the underlying reasons behind parents' decision to designate Arabic as their children's first language and the role of religious educational institutions in fostering the development of Arabic in the village. Employing a qualitative approach with netnographic methods, data collection was conducted through observations of social media accounts and interviews with informants. The findings reveal that a deep appreciation for Arabic, its use as a medium for memorizing the Qur'an, and the influence of alumni from Middle Eastern institutions are key factors behind parents' decisions to make Arabic their children's first language (L1). Religious educational institutions play a vital role in advancing Arabic as a cornerstone of civilization in Parmeraan Village by creating a language-rich environment and enhancing awareness and motivation to learn Arabic. The implications of this study highlight that religious awareness and parental education play a significant role in shaping children's language preferences, which can be broadly applied to efforts aimed at enhancing religious literacy through Arabic language acquisition.